Formulasi Strategi Penggunaan Jenis Pesawat PT Garuda Indonesia Dalam Persaingan Tahun 2019 - Charles AN; R. F. Ramadhanny (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
PT Garuda Indonesia should pay attention to which routes contribute significantly to the company. Therefore, it is necessary to formulate a strategy for the flight route, one of which is the use of aircraft types that are the company's primary consideration for achieving profit targets. The problem in this research was how to formulate strategies for the use of PT Garuda Indonesia aircraft types. Garuda Indonesia CGK-SIN-CGK route in 2019. The level of competition of PT Garuda Indonesia on the CGK-SIN-CGK route ranked second in the market on this route. According to CPM's matrix, the company ranks second. In 2018 on the route CGK-SIN-CGK, PT Garuda Indonesia used Airbus 330-200, Airbus 330-300, Boeing 737-800, Boeing 777-300 and Boeing 737-Max, 8 aircrafts with a total frequency of 6,315 flights and 844,714 pax. The average passengers that could be transported was 134 pax / flight and actually could be transported sufficiently by a narrow-body aircraft, that was, the Boeing 737-800 with the capacity of 162 seats (12C / 150Y). In the decision stage, the QSPM matrix was used. The product development strategy that can be implemented is that the company uses Boeing 737-800NG aircraft with a low total operating cost of the aircraft as the highest priority and followed by the second priority. In other words, the company uses a large-capacity 330 series Airbus aircraft.